Cerium speciation in silicate glasses: Structure-property relationships - Cicconi, Maria Rita; Veber, Alexander; Neuville, Daniel R.; Baudelet, François; de Ligny, Dominique (Journal of Non-Crystalline Solids, 2021)
Ascertaining elements oxidation state, coordination, and bonding environment provides an understanding of the parameters controlling the elements structural behavior, and in turn, the possibility of developing novel applications. Cerium doped materials are widely used for technological applications, mainly because of the strong UV absorption and the characteristic short decay time of the intense emission in the UV–Vis ranges. In this study, Ce speciation in different glass systems has been evaluated and related to variations in optical and physical properties, as well as to variations in glass network connectivity. Data obtained from X-ray Absorption Spectroscopy, Raman, and Photoluminescence Spectroscopy are presented. By using a multispectroscopy approach, we determined the Ce3+/Ce4+ redox ratio in silicate glasses/melts and the influence of the two different Ce species on structure and properties. Our study indicates that reduced Ce species are favored with an increase in the degree of melt polymerization but hindered in alkaline-rich bulk chemistries. Consequently, the oxygen ion activity (here represented by the theoretical optical basicity) might be used to estimate the Ce redox ratio's evolution. On the contrary, we show that glass luminescence properties cannot be tailored by merely adjusting the bulk chemistry. Furthermore, we propose an alternative approach for detecting and quantifying the different Ce species in glasses, and we show the occurrence of a non-symmetric Raman vibration at 880 cm−1, whose intensity is well correlated with the Ce3+/Ce4+ redox ratio. We assign this band to the interaction of the SiO4 tetrahedra with Ce4+-O polyhedral. Thus, cerium preferentially links to the silicate network, and we examined the possibility of using Raman spectroscopy to detect and quantify the different Ce species.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Photoluminescence; Raman; REE; Structural role; XAS